Regional Hemodynamics of the Brain and Psychosomatic Status in Patients Preoperating about Dissecting Aneurysm of the Aorta - E. V. Rybakova; A. Y. Lagutin; E. A. Nastenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
With the aim of studying the relationship of regional cerebral hemodynamics with cardiac surgery psychosomatic status of patients with pathology of the aorta were examined in 95 patients who underwent surgery in cardiopulmonary bypass, deep hypothermia using retrograde cerebral perfusion. Defined the new parameters of the functional connection between psychosomatic conditions and the data of Doppler ultrasound of the cerebral arteries. Diastolic flow velocity in the major arteries of the brain, when depresivnich disorders 1.4 times less than the normies, but at cognitive deficit is 3.2 times less than the normies. The obtained boundary values allow you to make the choice in favor of a specific diagnosis of a psychosomatic disorder.